Constructing responsibility in social interaction: an analysis of responsibility talk in hospital administrative groups - Eveliina Pennanen; Leena Mikkola (Qualitative Research in Medicine & Healthcare, 2018)
The role of responsibility in hospitals is undeniable. Although administrative groups are essential to organizational performance, previous group and team studies of responsibility in hospital organizations have concentrated mainly on healthcare teams. This study aims to describe and understand responsibility construction in the social interaction in hospital administrative group meetings, based on observation and analysis of seven administrative group meetings in a Finnish hospital. Categories generated by thematic content analysis were compared with responsibility types. The findings show that responsibility is constructed by creating co-responsibility, taking individual responsibility, and constructing non-responsibility. Action and role and task responsibilities emerged as types from the interaction. To support employee involvement in responsibility processes, they must also be provided with sufficient resources to deal with that responsibility and to manage its different dimensions. These insights can be utilized to improve administrative groups.